2020
DOI: 10.21203/rs.2.21516/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of mass media exposure on Tuberculosis knowledge and attitude among migrant and seasonal farmworkers in Northwest Ethiopia

Abstract: Background Globally, tuberculosis (TB) is the 9 th leading cause of death. Despite no country achieved its target, the world health organization (WHO) proposed a 90-90-90 approach to fastening the end TB strategy. Improvement and progression of TB control need good knowledge and a favorable attitude towards the disease. However, interventions designed don’t take migrants and seasonal farmworkers into account. Therefore, this study aimed at estimating the level of knowledge and attitude on Tuberculosis among mi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Tis was refected in our fndings also, i.e., with increased income level (wealth index) the chances of getting access to education, better living conditions, exposure to mass media (television, radio, and Internet), and medicare increases. Numerous studies have shown that mass media infuences people's behaviour [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Tis was refected in our fndings also, i.e., with increased income level (wealth index) the chances of getting access to education, better living conditions, exposure to mass media (television, radio, and Internet), and medicare increases. Numerous studies have shown that mass media infuences people's behaviour [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, they are exposed to poor living and working conditions, they work physically demanding jobs, most of the time away from their families, and they have limited access to healthcare services (7). For some, living and working conditions, coupled with migration status, exacerbates their vulnerability to HIV (7,8). Agricultural workers are further described as a highly mobile population, as they tend to be internal or external migrants, and most likely to work from farm to farm, which is driven by the seasonal nature of their work (9).…”
Section: Introductionmentioning
confidence: 99%